2012
DOI: 10.1504/ijep.2012.051189
|View full text |Cite
|
Sign up to set email alerts
|

WRF evaluation exercise using open sea in situ measurements

Abstract: The quality of the prediction of the atmospheric transport and dispersion of toxic, hazardous materials and pollutants strongly depends on the atmospheric forcing and in particular on the wind field. Especially in coastal regions, another important factor for correctly predicting the pollutant levels is the precise quantification of the sea aerosol particles formed predominantly by the action of the wind on the ocean surface. Furthermore, acting as a cloud condensation nuclei to form cloud drops, exchanging ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Our results, as well as previous results reporting better agreement with observations of the MM5 using 12 km resolution over a finer resolution (URS Corporation, 2008;Zhang et al, 2011) and differences between models in prediction of the surface wind direction (Balzarini et al, 2012), reveal that a detailed and careful assessment is required when applying meteorological models to study pollutant dispersion as part of environmental impact surveys (EIS) or for regulatory purposes. Table 4 Comparison over the whole year of 2011 of surface wind predictions of the MM5 and WRF meteorological models with observations.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our results, as well as previous results reporting better agreement with observations of the MM5 using 12 km resolution over a finer resolution (URS Corporation, 2008;Zhang et al, 2011) and differences between models in prediction of the surface wind direction (Balzarini et al, 2012), reveal that a detailed and careful assessment is required when applying meteorological models to study pollutant dispersion as part of environmental impact surveys (EIS) or for regulatory purposes. Table 4 Comparison over the whole year of 2011 of surface wind predictions of the MM5 and WRF meteorological models with observations.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, overestimated annual average wind speed is obtained for the complex terrain conditions. These results are in agreement with the findings of Balzarini et al (2012), who reported no systematic tendency of WRF towards underestimation or overestimation of the surface wind speed. Our results do not support, however, Liu and Warner (2004)'s conclusions that MM5 predictions of surface wind speed and direction are more accurate than those of WRF.…”
Section: Surface Wind Fieldsupporting
confidence: 93%
See 3 more Smart Citations